1990
DOI: 10.5670/oceanog.1990.07
|View full text |Cite
|
Sign up to set email alerts
|

Richard W. Eppley's Contributions to Phytoplankton Physiology and Biological Oceanography

Abstract: Richard 14,: Epplev has established himself as one ~f ttte most iJ!fluential biological oceanographers of this century through his contributions to the fieM of phytoplankton physiological ecology and his interdisciplinary approach to oceanographic processes. Dick's ability to generalize and conceptualize, to take separate threads of research and weave them into a cohesive fi'amework, has enabled hint to use established techniques in novel appli~'ations, to define new approaches to old oceanographic questions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Preliminary models of VLA observations suggest an average mass-loss of ∼ 2.5 × 10 −4 M ⊙ year −1 , assuming wind-driven, clumpy/filamentary CSM Stockdale et al 2007). Weiler et al (2002) indicates that such a radio-derived mass-loss rate is slightly higher than values determined for other type IIn SNe, 1.14×10 −4 M ⊙ year −1 for SN 1988Z and 4.28×10 −5 M ⊙ year −1 for SN 1986J. However, depending on when this shell of material was ejected, the actual mass-loss event was likely much higher than this average value.…”
Section: Discussionmentioning
confidence: 68%
“…Preliminary models of VLA observations suggest an average mass-loss of ∼ 2.5 × 10 −4 M ⊙ year −1 , assuming wind-driven, clumpy/filamentary CSM Stockdale et al 2007). Weiler et al (2002) indicates that such a radio-derived mass-loss rate is slightly higher than values determined for other type IIn SNe, 1.14×10 −4 M ⊙ year −1 for SN 1988Z and 4.28×10 −5 M ⊙ year −1 for SN 1986J. However, depending on when this shell of material was ejected, the actual mass-loss event was likely much higher than this average value.…”
Section: Discussionmentioning
confidence: 68%
“…Instead, these subsurface Chl maxima generally represent ecologically significant features of the planktonic ecosystemcontiguous layers of phytoplankton that are nearly ubiquitous in stratified waters and that have attracted focused examination since benchmark modeling studies by Gordon Riley and John Steele (Riley et al 1949;Steele 1956Steele , 1964Steele & Yentsch 1960) and some of the first continuous vertical profiles of chlorophyll fluorescence that revealed previously unappreciated features in the vertical distributions of phytoplankton (Strickland 1968). My studies of subsurface chlorophyll maximum layers (SCMLs) began nearly 40 years ago under the supervision of Richard W. Eppley, one of the most influential biological oceanographers of the twentieth century (Weiler et al 1990). His guidance on how to approach this scientific problem is as appropriate now as it was then.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking better opportunities for his growing family after teaching at the University of Southern California (1957California ( -1960, he took a research position with the Northrop Corporation (1960)(1961)(1962)(1963) where he worked on culturing algae for life support in space vehicles. In a tribute published shortly after his retirement in 1989 (Weiler et al 1990), Dick Eppley's eight Ph.D. students and four postdoctoral researchers (Table 2) reviewed his important contributions to pursuits that had become central to modern biological oceanography at the time. These included: The 1990 article describing Eppley's research provides a roadmap to a trove of information on his publications and their impacts at that time.…”
Section: Figmentioning
confidence: 99%
“…Recognizing the breadth, depth, and insight of his research, Dick's students and postdocs concluded that "Richard W. Eppley has established himself as one of the most influential biological oceanographers of this century through his contributions to the field of phytoplankton physiological ecology and his interdisciplinary approach to oceanographic processes" (Weiler et al 1990). As illustrated with a few examples of key papers in Table 1, Dick's work has continued to influence the direction of oceanographic research well into the 21 st century and it is clearly foundational for studies of phytoplankton dynamics and biogeochemical cycles.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation